High functional diversity of forest ecosystems is linked to high provision of water flow regulation ecosystem service. (August 2020) - Esquivel, Jocelyn; Echeverría, Cristian; Saldaña, Alfredo; Fuentes, Rodrigo
Highlights: Water flow regulation variability is linked to spatio-temporal biodiversity change. Landscape legacies are related to loss of functional diversity. In low functional diversity water flow regulation may vary depending on forest type. Water flow regulation is stably high in functional diversity ≥0.3. Biodiversity thresholds can enhance watersheds planning for better water regulation. Abstract: Ecosystem services, the direct or indirect contributions of ecosystems to human well-being, are based on interactions that occur within complex systems at different ecological levels. The strong link between biodiversity and ecosystem services is an important argument for ecosystem management and conservation. In this study we quantified the link between the functional diversity (FD)- used as a proxy of biodiversity- of different forest ecosystems and their water flow regulation (WFR) ecosystem service. This link was evaluated over time and space in two contrasting landscapes of south-central Chile, with different legacies of land use/cover change (LUCC), between 1986 and 2011. We calculated a subwatershed-averaged FD, based on the functional divergence of forest ecosystems at each subwatershed in both landscapes. To evaluate WFR we used a spatially explicit hidrological-model-based indicator. The results revealed a positive linkage between forest ecosystems biodiversity and the provision of WFR. Greater FD was spatially associated with higher WFR provision rates with the FD = 0.3 being a critical threshold for high WFR rates. However, some subwatersheds with lower FD values also had high WFR rates. This may be related to the presence of mono-specific forest plantations, which lack diversity, but fulfill important functions in the hydrological cycle as a result of their structure. We conclude that FD has a positive spatial relationship with WFR, where WFR is the result of the multiple ecosystem processes such as energy exchange, evapotranspiration, runoff. FD, evaluated at the ecosystem level, can be a good means to quantify the link between biodiversity and ecosystem services. This type of analysis may be used to allow us to evaluate the thresholds of biodiversity necessary to maintain a target magnitude of the ecosystem service over time in a given watershed.